2012
DOI: 10.1177/0269881112467089
|View full text |Cite
|
Sign up to set email alerts
|

A review of anti-inflammatory agents for symptoms of schizophrenia

Abstract: Schizophrenia is a chronic debilitating mental disorder that affects about 1% of the U.S population. The pathophysiology and etiology remain unknown, thus new treatment targets have been challenging and few novel treatments with new mechanisms of action have come to market in the past few decades. Increasing attention has been paid to the role of inflammation in schizophrenia and new data suggests that decreasing inflammation and inflammatory biomarkers may play some role in schizophrenia treatment. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 51 publications
0
67
0
2
Order By: Relevance
“…Lastly, based on the neuroinflammatory hypothesis of schizophrenia (Kirkpatrick and Miller, 2013;Na et al, 2014) and that some patients benefit from the effects of adjunct anti-inflammatory therapies (Keller et al, 2013;Sommer et al, 2012), this could be another mechanism by which CBD may exert its antipsychotic effects. This hypothesis is supported by evidence which has shown that CBD has anti-inflammatory properties (Burstein, 2015).…”
Section: Potential Mechanisms Of Antipsychotic Effectmentioning
confidence: 99%
“…Lastly, based on the neuroinflammatory hypothesis of schizophrenia (Kirkpatrick and Miller, 2013;Na et al, 2014) and that some patients benefit from the effects of adjunct anti-inflammatory therapies (Keller et al, 2013;Sommer et al, 2012), this could be another mechanism by which CBD may exert its antipsychotic effects. This hypothesis is supported by evidence which has shown that CBD has anti-inflammatory properties (Burstein, 2015).…”
Section: Potential Mechanisms Of Antipsychotic Effectmentioning
confidence: 99%
“…The remission of psychotic symptoms in this patient has been associated with maintenance of the gluten-free diet, but it is also possible that the minocycline he was taking for acne contributed to his recovery, since this antibiotic has been associated with improvement of schizophrenia symptoms in several studies (22, 23). However, both risperidone and minocycline have since been discontinued.…”
Section: Discussionmentioning
confidence: 87%
“…For example, add-on antiinflammatory agents could be used in conjunction with existing antipsychotics to target these molecules and their pathways (Keller et al, 2013). This approach is discussed in further detail in Section 4.…”
Section: Potential Confounding Effects Of Psychological Stress and Otmentioning
confidence: 99%